2010
DOI: 10.1128/iai.00593-10
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical, Domain Type-Specific Acquisition of Antibodies to Plasmodium falciparum Erythrocyte Membrane Protein 1 in Tanzanian Children

Abstract: Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) is a variant antigen expressed on the surface of malaria-infected erythrocytes. PfEMP1 attaches to the vascular lining and allows infected erythrocytes to avoid filtration through the spleen. Each parasite genome encodes about 60 different PfEMP1 variants, each PfEMP1 comprises several domains in its extracellular region, and the PfEMP1 repertoire in different parasites contains domain types that are serologically cross-reactive. In this longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
12
63
0
Order By: Relevance
“…47). Parasites expressing group A PfEMP1 proteins occur predominantly among children with limited immunity (7), and IgG to this group of Ags is acquired faster than IgG to other PfEMP1 groups (48,49) and appear to be more cross-reactive (39,50). The data presented in this study underpin these earlier findings and support the hypothesis that IgG to relatively conserved and functionally important Ab epitopes in group A PfEMP1 proteins are of importance in acquisition of clinical immunity to malaria.…”
Section: Discussionsupporting
confidence: 80%
“…47). Parasites expressing group A PfEMP1 proteins occur predominantly among children with limited immunity (7), and IgG to this group of Ags is acquired faster than IgG to other PfEMP1 groups (48,49) and appear to be more cross-reactive (39,50). The data presented in this study underpin these earlier findings and support the hypothesis that IgG to relatively conserved and functionally important Ab epitopes in group A PfEMP1 proteins are of importance in acquisition of clinical immunity to malaria.…”
Section: Discussionsupporting
confidence: 80%
“…The fact that most DC8 var genes have mixed features (UpsB promoter and group A coding features) could limit gene recombination with other group A or group B genes and favor the evolution of specialized adhesion properties within group B/A genes. Significantly, DC8 var products tend to be among the first PfEMP1s expressed in early childhood infections (15,16), indicating they may encode unique adhesion properties that confer a growth advantage in malaria-naive children. This study demonstrates that DC8 var products can encode binding activity for brain endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most PfEMP1 proteins bind CD36, group A and the related group B/A have a distinct protein head structure from other var groups (8,9) and do not bind CD36 (13,14). Group A and B/A proteins also tend to be among the first PfEMP1 proteins expressed in early childhood infections (15)(16)(17)(18) and have been associated with more severe infections (18)(19)(20)(21), but whether they have affinity for brain endothelium is unknown. Studies of malaria during pregnancy have demonstrated how a single var gene, VAR2CSA, is primarily responsible for placenta binding (22)(23)(24).…”
mentioning
confidence: 99%
“…In contrast, FV6 and FV60 are encoded by var genes that are transcribed and translated independent of pregnancy, and they represent rosetting PfEMP1 proteins thought to be involved in the pathogenesis of severe malaria in childhood (31). People living in areas with stable transmission of P. falciparum parasites are thought to be exposed regularly to parasites expressing this type of PfEMP1 proteins (32,33,64,65).…”
Section: Discussionmentioning
confidence: 99%